Festive Ukrainian cooking - Farley, Marta Pisetska (University of Pittsburgh Press, 1990)
Shares menus for traditional Ukrainian feasts and family celebrations, and includes recipes for appetizers, soups, salads, breads, meat, poultry, fish, vegetables, and desserts.